2018
DOI: 10.1016/j.annemergmed.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Getting Inside the Expert’s Head: An Analysis of Physician Cognitive Processes During Trauma Resuscitations

Abstract: The novel approach of cognitive task analysis augmented by eye tracking allowed the derivation of 5 unique cognitive processes underpinning expert performance in leading a resuscitation. An understanding of these cognitive processes has the potential to enhance educational methods and to create new assessment modalities of these previously tacit aspects of expertise in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Recent publications show its effectiveness assessing or evaluating in simulating scenarios related to anaphylaxis or paediatric trauma [12,22]. In fact, the accuracy of this tool also resulted in its using in real situations [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications show its effectiveness assessing or evaluating in simulating scenarios related to anaphylaxis or paediatric trauma [12,22]. In fact, the accuracy of this tool also resulted in its using in real situations [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds to existing knowledge of the application of eye tracking in medical education, but is the first of its kind in pediatric trauma. [5][6][7] In neonatal resuscitation, gaze preference amongst six expert consultants was focused primarily towards the monitor rather than the neonate. 8 In a simulated pediatric intensive care unit (PICU) environment, expert consultants focused their gaze predominantly on the chest and airway of the patient, whereas novice clinicians had visual preference directed towards the defibrillator.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we hope to compare and contrast eye-tracking behaviours in trainees versus attending physicians. 7 Assuming that experts have a better sense of what is important to focus on, contrasting this to trainee's visual fixation may identify opportunities for behaviour change. 10 Secondly, we hope to study visual eye tracking in other high-stakes clinical contexts (e.g., cardiac arrest) and during technical skills (e.g., intubation).…”
Section: Discussionmentioning
confidence: 99%
“…Although some elements of CRM performance are observable, (and therefore able to be assessed and studied with currently available tools), other elements, such as the cognitive processes that underlie CRM skills, are not (White et al, 2018). Our understanding of these invisible cognitive processes remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In studying trauma team leaders in real clinical settings, we have previously demonstrated that a post-hoc cognitive task analysis augmented by review of first person video generated by an eye-tracking device is a useful technique to uncover these cognitive processes (White et al, 2018). In that study, expert trauma team leaders were found to demonstrate logistic awareness, manage uncertainty, strategically direct their gaze, selectively attend to information, and exhibit anticipatory behaviours while treating critically injured patients.…”
Section: Introductionmentioning
confidence: 99%